Desain Pembelajaran pada Teori Dasar Peluang Menggunakan Permainan UNO: Usaha Meningkatkan Pemahaman Konsep Peluang - Ziliwu, Farisman; Febri, Febi; Nur Hidayatullah, Muhammad Alif; Subekti, Retno (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
UNO cards are a game that can be played by all groups. Currently, UNO is a game that is often used, so UNO cards as a learning medium is expected to attract students' attention and involvement. Therefore, studies are needed to see how effective UNO cards as a learning medium and researchers promote learning designs using the HLT method to support learning probability using UNO media because of the need for didactic teaching in probability. This literature review took a total of 10 journal articles published in the 2018-2023. The results obtained showed that UNO cards as a learning medium was proven to be effective in helping mathematical thinking skills. The effectiveness of UNO cards as a learning medium in collaboration with HLT approach to develop learning designs for opportunity materials in junior high schools. Guided reinvention from the teacher is adapted to class conditions, and additional activities can also be adjusted to bridge understanding for students.